How do you find the derivative of y=e^(-2x-1) * ln(-2x-1)? Calculus Differentiating Exponential Functions Differentiating Exponential Functions with Base e 1 Answer Gav Jun 21, 2018 -e^(-2x-1)/(-2x-1)-2ln(-2x-1)e^(-2x-1) Explanation: d/dxln(-2x-1)e^(-2x-1) =d/dx[ln(-2x-1)]*e^(-2x-1)+ln(-2x-1)*d/dx(e^[-2x-1]) =1/(-2x-1)*d/dx(-2x-1)*e^[-2x-1]+e^[-2x-1]*d/dx[-2x-1]*ln(-2x-1) ={(-2*d/x[x]+d/dx[-1])e^[-2x-1]}/[-2x-1]+(-2*d/x[x]+d/dx[-1])ln(-2x-1)e^(-2x-1) =[(0-2*1)e^(-2x-1)]/[-2x-1]+(0-2*1)ln(-2x-1)e^(-2x-1) =-e^(-2x-1)/(-2x-1)-2ln(-2x-1)e^(-2x-1) Answer link Related questions What is the derivative of y=3x^2e^(5x) ? What is the derivative of y=e^(3-2x) ? What is the derivative of f(theta)=e^(sin2theta) ? What is the derivative of f(x)=(e^(1/x))/x^2 ? What is the derivative of f(x)=e^(pix)*cos(6x) ? What is the derivative of f(x)=x^4*e^sqrt(x) ? What is the derivative of f(x)=e^(-6x)+e ? How do you find the derivative of y=e^x? How do you find the derivative of y=e^(1/x)? How do you find the derivative of y=e^(2x)? See all questions in Differentiating Exponential Functions with Base e Impact of this question 3331 views around the world You can reuse this answer Creative Commons License